Recent advances of monoelemental 2D materials for photocatalytic applications - Hu, Rong; Liao, GengCheng; Huang, Zongyu; Qiao, Hui; Liu, Huating; Shu, Yiqing; Wang, Bing; Qi, Xiang (Journal of hazardous materials, 2021)
As a sustainable environmental governance strategy and energy conversion method, photocatalysis has considered to have great potential in this field due to its excellent optical properties and has become one of the most attractive technologies today. Among 2D materials, the emerging two-dimensional (2D) monoelemental materials mainly distributed in the -IIIA, -IVA, -VA and -VIA groups and show excellent performance in solar energy conversion due to their graphene-like 2D atomic structure and unique properties, thereby drawing increasing attention. This review briefly summarizes the preparation processes and fundamental properties of 2D single-element nanomaterials, as well as various modification strategies and adjustment mechanisms to enhance their photocatalytic properties. In particular, this article comprehensively discusses the related practical applications of 2D single-element materials in the field of photocatalysis, including photocatalytic degradation for contaminants removal, photocatalytic pathogen inactivation, photocatalytic fouling control and photocatalytic energy conversion. This review will provide some new opportunities for the rational design of other excellent photocatalysts based on 2D monoelemental materials, as well as present tremendous novel ideas for 2D monoelemental materials in other environmental conservation and energy-related applications, such as supercapacitors, electrocatalysis, solar cells, and so on. [Display omitted] •The preparation and fundamental properties of 2D single-element nanomaterials were discussed.•The mechanism of photocatalysis and enhanced strategies based on it were exhibited here.•The recent photocatalytic applications of 2D monoelemental materials were reviewed in detail.•The challenges encountered and further perspectives were presented.